Personality features in a group of alcohol dependence patients - Sayın, Aslıhan; Karslıoğlu, Ersin; Arıkan, Zehra; Aslan, Selçuk (Journal of Dependence, 2004)
Objective: TPQ (Tridimensional Personality Questionnaire) is the first version of a self-evaluating personality questionnaire, which was proposed by Cloninger, who later developed a more precise and complete version called TCI (Temperament and Character Inventory). Both have been used in several studies on personality features of psychiatric disorders, and Cloninger’s alcoholism typology (Type I and II alcoholism). The purpose of this study was to evaluate the correlation between depression, anxiety, character and personality features of alcoholic patients.Method: 25 patients at early remission and 25 patients who have been at remission for at least 6 months and who have been diagnosed as Alcohol Dependency according to DSM-IV-TR were evaluated. 12 questioned sociodemografic information questionnaire, Zung Depression Scale, STAI I and II Anxiety Scale, Cage, TCI were given to all patients. Received data was analyzed by SPSS (Windows 11.0) programe and t-test for independent samples was used. The statistical results were considered significant for p
Keywords: Personality features; alcoholism; temperament; character; depression; anxiety